The adductor pollicis muscle thickness is not associated with physical function, lean mass, and nutritional status in patients on maintenance hemodialysis - Morais, Débora Moreira; Trombim, Isadora Cordeiro; de Góes, Cassiana Regina; Vogt, Barbara Perez (Frontiers in Nutrition, 2025)
BackgroundThe adductor pollicis muscle thickness (APMT) may be associated with the muscle strength in patients on hemodialysis. However, the association of APMT with other physical function assessment tests has not yet been tested. Moreover, because it is considered a good nutritional indicator and not influenced by fluid overload, the APMT may be associated with the muscle mass and nutritional status of these patients. Therefore, the objective was to assess the association of APMT with physical function, muscle mass and nutritional status in patients on hemodialysis.MethodsThe APMT was measured using a skinfold caliper between pollicis finger and index finger. Physical function was evaluated by handgrip strength (HGS), Short Physical Performance Battery (SPPB), the sit-to-stand test, gait speed test, and timed up and go (TUG). Appendicular muscle mass index (AMMI) was estimated using bioelectrical impedance. The nutritional status was evaluated by the Malnutrition Inflammation Score (MIS).ResultsFifty-one patients were included, 60.8% men, mean age 58.4 ± 12.6 years. There were no significant correlations of APMT with physical function, muscle mass and nutritional status. Values of APMT were not different between the groups according to adequate physical function or muscle mass. In the multiple linear regression analysis adjusted for sex, age and diabetes, APMT was not significantly associated with physical function tests, as HGS (β = 0.101; p = 0.778), gait speed (β = −0.014; p = 0.180), SPPB (β = −0.054; p = 0.590), TUG (β = 0.202; p = 0.109), lean mass AMMI (β = 0.058; p = 0.147).ConclusionThere were no associations of APMT with physical function, muscle mass and nutritional status in patients on hemodialysis. We suggest APMT should not be used in physical function and nutritional assessments of these patients.